Effectiveness of Interactive Multimedia Based on Project Based Learning to Enhance Student Learning Creativity - Nova Nurlaili Zakyani; Arif Widiyatmoko (Universitas Negeri Semarang, 2025)
This research aims to determine the effectiveness of using interactive multimedia based on project-based learning on the creativity of students regarding the human respiratory system material in the 8th grade of MTs Negeri Kota Depok. The type of research used in this study is experimental research with a pre-experimental design in the form of a one group pretest posttest design, with a quantitative research approach. In this research, sampling was conducted using total sampling technique with class 8 F as the research sample. The results showed that the average score of student learning outcomes after the application of powtoon learning media was 81.5625 while before being treated was 36.015625. In addition, there was an increase in student learning outcomes after the implementation of project-based learning-based interactive multimedia by obtaining an average gain value of 0.712 which was at high criteria. As for the n-gain percent obtained 71.2, it is on the criteria of being quite effective. From the results of this study, it can be concluded that the use of interactive multimedia based on project-based learning is effective in enhancing students’ creativity in the material of the human respiratory system for eighth-grade students at MTs Negeri Kota Depok.